Accommodating Social Security and Freedom of Religion. Issue 3 (September 2015) - Pieters, Danny
In this article I explore how national and European law deal with situations where the right to social security, and, more broadly, the law on social security, seem to conflict with the freedom of religion. The article begins by specifying what is meant by the terms 'social security' and 'freedom of religion'. It attempts to illustrate areas of real or apparent conflict between the freedom of religion and social security law, referring to case law and practice in a variety of Western countries. It then deals with religious objections to participation in social security schemes as such, with the definition of suitable work from a religious perspective and with health care coverage in light of religious objections. In conclusion, it seeks to develop an approach that can be followed for solving cases of real or apparent tension between social security law and the freedom of religion.